IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Devisa, Kresensia Ranti; Aunurrahman, Aunurrahman; Halida, Halida; T, Ahmad Yani; Waruwu, Marinu (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to analyze the implementation of the principal’s academic supervision in improving the quality of teachers’ instruction at SD Negeri 17 Pontianak Kota. The research employed a qualitative method with a case study approach. Data were collected through semi-structured interviews, direct observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana. The findings revealed that academic supervision was implemented systematically through three main stages: needs-based planning, collaborative implementation using multiple methods, and continuous evaluation and follow-up. This implementation had a significant impact on improving teachers’ pedagogical and professional competencies, as well as transforming teachers’ perceptions of supervision from mere monitoring into professional guidance. It can be concluded that structured, collaborative, and continuous academic supervision is effective in enhancing the quality of teaching. Key success factors include strong leadership commitment, active teacher involvement, a humanistic approach, proper documentation, and adequate resource support.